Interorganizational Coordination On Car Free Day For Low Carbon Transportation - Wahyudin, Dian; Widianingsih, Ida; Abdullah, Oekan A (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The transportation sector is one of the main contributors to the impact on environmental change due to its role in air pollution, greenhouse gases and CO2 emissions. Effective action is needed to limit the environmental impact of transportation activities. Jakarta is one of the most polluted cities in the world. The DKI Jakarta Provincial Government runs a Car Free Day (CFD) with the aim of reducing pollution and the use of public transportation. This study aims to determine the impact of CFD implementation and inter-organizational coordination that occurs in the implementation of CFD. The research method uses in-depth interviews with participants. The results show that CFD is not optimal in reducing air pollution, but it is very good for programs as a good health campaign tool, getting used to a healthy lifestyle and as a public space. However, the implementation must be improved starting from spatial planning and waste management. Meanwhile, coordination between organizations is still sectoral to achieve the goals of each SKPD